Analysis of Factors Inhibiting Supplementary Feeding (PMT) in Undernourished Toddlers in the Region Work of the Botupingge Health Center - Sry Fazria Supu; Sunarto Kadir; Suardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Malnutrition in toddlers is still one of the health problems that needs attention because it can affect children's growth and development. One of the efforts made to overcome this problem is through the Supplementary Feeding (PMT) program, either PMT Recovery or Counseling. Therefore, the formulation of the problem in this study is whether there is a relationship between maternal compliance, culture, and social environment with barriers to supplemental feeding (PMT) in undernourished toddlers in the working area of the Botupingge Health Center. This study aims to analyze the factors that hinder the provision of additional food (PMT) in undernourished toddlers in the working area of the Botupingge Health Center. This study uses quantitative research with an analytical observational method using a cross sctional design. The research sample amounted to 48 respondents who were determined by total sampling technique. Data was collected using a questionnaire and analyzed using the Spearman Rank test. The results showed that most of the respondents had a fairly compliant level of the mothers category, the culture of the category was quite supportive, the social environment of the category was quite supportive, and the provision of PMT categories was quite good. The results of the Spearman's Rank Test analysis resulted in values of p=0.005 and r=0.399 for the maternal compliance variable, p=0.086 and r=0.251 for the cultural variable, and p=0.027 and r=0.318 for the social environment variable. The conclusion of this study shows that maternal compliance and the social environment are related to the administration of PMT in undernourished toddlers, while culture is not related to the administration of PMT. Therefore, the role of mothers and social environmental support are needed in supporting the provision of PMT to undernourished toddlers.